A Bayesian Approach to Predict Solubility Parameters - Sanchez-Lengeling, Benjamin; Roch, Loïc; Perea Ospina, Jose Dario; Langner, Stefan; Brabec, Christoph; Aspuru-Guzik, Alan (Advanced Theory and Simulations, 2019)
Solubility is a ubiquitous phenomenon in many aspects of material science. While solubility can be determined by considering the cohesive forces in a liquid via the Hansen solubility parameters (HSP), quantitative structure-property relationship models are often used for prediction, notably due to their low computational cost. Here, gpHSP, an interpretable and versatile probabilistic approach to determining HSP, is reported. Our model is based on Gaussian processes, a Bayesian machine learning approach that provides uncertainty bounds to prediction. gpHSP achieves its flexibility by leveraging a variety of input data, such as SMILES strings, COSMOtherm simulations, and quantum chemistry calculations. gpHSP is built on experimentally determined HSP, including a general solvents set aggregated from the literature, and a polymer set experimentally characterized by this group of authors. In all sets, a high degree of agreement is obtained, surpassing well-established machine learning methods. The general applicability of gpHSP to miscibility of organic semiconductors, drug compounds, and in general solvents is demonstrated, which can be further extended to other domains. gpHSP is a fast and accurate toolbox, which could be applied to molecular design for solution processing technologies.
Keywords: machine learning; miscibility; organic materials; polymers; solubility

A bilayer conducting polymer structure for planar perovskite solar cells with over 1,400 hours operational stability at elevated temperatures - Zhao, Yicheng; Heumueller, Thomas; Zhang, Jiyun; Luo, Junsheng; Kasian, Olga; Langner, Stefan; Kupfer, Christian; Liu, Bowen; Zhong, Yu; Elia, Jack; Osvet, Andres; Wu, Jianchang; et al. (Nature Energy, 2021)
The long-term stability of perovskite solar cells remains a challenge. Both the perovskite layer and the device architecture need to endure long-term operation. Here we first use a self-constructed high-throughput screening platform to find perovskite compositions stable under heat and light. Then, we use the most stable perovskite composition to investigate the stability of contact layers in solar cells. We report on the thermal degradation mechanism of transition metal oxide contact (for example, Ta-WOx/NiOx) and propose a bilayer structure consisting of acid-doped polymer stacked on dopant-free polymer as an alternative. The dopant-free polymer provides an acid barrier between the perovskite and the acid-doped polymer. The bilayer structure exhibits stable ohmic contact at elevated temperatures and buffers iodine vapours. The unencapsulated device based on the bilayer contact (with a MgF2 capping layer) retains 99% of its peak efficiency after 1,450 h of continuous operation at 65 degrees C in a N-2 atmosphere under metal-halide lamps. The device also shows negligible hysteresis during the entire ageing period.
CRIS-Team WoS Importer:2021-12-24

Abnormal strong burn-in degradation of highly efficient polymer solar cells caused by spinodal donor-acceptor demixing - Li, Ning; Perea, José Darío; Kassar, Thaer; Richter, Moses; Heumüller, Thomas; Matt, Gebhard; Hou, Yi; Güldal, Nusret Sena; Chen, Haiwei; Chen, Shi; Langner, Stefan; Berlinghof, Marvin; et al. (Nature Communications, 2017)
The performance of organic solar cells is determined by the delicate, meticulously optimized bulk-heterojunction microstructure, which consists of finely mixed and relatively separated donor/acceptor regions. Here we demonstrate an abnormal strong burn-in degradation in highly efficient polymer solar cells caused by spinodal demixing of the donor and acceptor phases, which dramatically reduces charge generation and can be attributed to the inherently low miscibility of both materials. Even though the microstructure can be kinetically tuned for achieving high-performance, the inherently low miscibility of donor and acceptor leads to spontaneous phase separation in the solid state, even at room temperature and in the dark. A theoretical calculation of the molecular parameters and construction of the spinodal phase diagrams highlight molecular incompatibilities between the donor and acceptor as a dominant mechanism for burn-in degradation, which is to date the major short-time loss reducing the performance and stability of organic solar cells.

Air-processed organic tandem solar cells on glass: Toward competitive operating lifetimes - Adams, Jens; Spyropoulos, Georgios; Salvador, Michael Filipe; Li, Ning; Strohm, Sebastian; Lucera, Luca; Langner, Stefan; Machui, Florian; Zhang, Hong; Ameri, Tayebeh; Voigt, Monika M.; Krebs, Frederik C.; et al. (Energy and Environmental Science, 2015)
Photovoltaic devices based on organic semiconductors (OPVs) hold great promise as a cost-effective renewable energy platform because they can be processed from solution and deposited on flexible plastics using roll-to-roll processing. Despite important progress and reported power conversion efficiencies of more than 10% the rather limited stability of this type of devices raises concerns towards future commercialization. The tandem concept allows for both absorbing a broader range of the solar spectrum and reducing thermalization losses. We designed an organic tandem solar cell with an inverted device geometry comprising environmentally stable active and charge-selecting layers. Under continuous white light irradiation, we demonstrate an extrapolated, operating lifetime in excess of one decade. We elucidate that for the current generation of organic tandem cells one critical requirement for long operating lifetimes consists of periodic UV light treatment. These results suggest that new material approaches towards UV-resilient active and interfacial layers may enable efficient organic tandem solar cells with lifetimes competitive with traditional inorganic photovoltaics.

Beyond Ternary OPV: High-Throughput Experimentation and Self-Driving Laboratories Optimize Multicomponent Systems - Langner, Stefan; Häse, Florian; Perea, Jose Dario; Stubhan, Tobias; Hauch, Jens; Roch, Loïc M.; Heumüller, Thomas; Aspuru-Guzik, Alán; Brabec, Christoph (Advanced Materials, 2020)
Fundamental advances to increase the efficiency as well as stability of organic photovoltaics (OPVs) are achieved by designing ternary blends, which represents a clear trend toward multicomponent active layer blends. The development of high-throughput and autonomous experimentation methods is reported for the effective optimization of multicomponent polymer blends for OPVs. A method for automated film formation enabling the fabrication of up to 6048 films per day is introduced. Equipping this automated experimentation platform with a Bayesian optimization, a self-driving laboratory is constructed that autonomously evaluates measurements to design and execute the next experiments. To demonstrate the potential of these methods, a 4D parameter space of quaternary OPV blends is mapped and optimized for photostability. While with conventional approaches, roughly 100 mg of material would be necessary, the robot-based platform can screen 2000 combinations with less than 10 mg, and machine-learning-enabled autonomous experimentation identifies stable compositions with less than 1 mg.
CRIS-Team Scopus Importer:2020-02-25
Keywords: high-throughput experimentation; machine learning; organic photovoltaics; photostability; solar energy

Classification of Additives for Organic Photovoltaic Devices - Machui, Florian; Maisch, Philipp; Burgues-Ceballos, Ignasi; Langner, Stefan; Krantz, Johannes; Ameri, Tayebeh; Brabec, Christoph (ChemPhysChem, 2015)
The use of additives to improve the performance of organic photovoltaic cells has been intensely researched in recent years. However, so far, no system has been reported for the classification of additives and their functions. In this report, a system for classifying additives according to the fundamental mechanism by which they influence microstructure formation for P3HT:PCBM is suggested. The major parameters used for their classification are solubility and drying kinetics. Both are discussed in detail and their consequences on processing are analyzed. Furthermore, a general mechanism to classify the impact of additives on structure formation is suggested and discussed for different materials relevant to organic photovoltaic devices.
Keywords: additives; fullerenes; ink formulation; organic photovoltaics; polymers

Combined Computational Approach Based on Density Functional Theory and Artificial Neural Networks for Predicting the Solubility Parameters of Fullerenes - Perea Ospina, Jose Dario; Langner, Stefan; Salvador, Michael Filipe; Kontos, Janos; Jarvas, Gabor; Winkler, Florian; Machui, Florian; Görling, Andreas; Dallos, Andras; Ameri, Tayebeh; Brabec, Christoph (Journal of Physical Chemistry B, 2016)
The solubility of organic semiconductors in environmentally benign solvents is an important prerequisite for the widespread adoption of organic electronic appliances. Solubility can be determined by considering the cohesive forces in a liquid via Hansen solubility parameters (HSP). We report a numerical approach to determine the HSP of fullerenes using a mathematical tool based on artificial neural networks (ANN). ANN transforms the molecular surface charge density distribution (σ-profile) as determined by density functional theory (DFT) calculations within the framework of a continuum solvation model into solubility parameters. We validate our model with experimentally determined HSP of the fullerenes C, PCBM, bisPCBM, ICMA, ICBA, and PCBM and through comparison with previously reported molecular dynamics calculations. Most excitingly, the ANN is able to correctly predict the dispersive contributions to the solubility parameters of the fullerenes although no explicit information on the van der Waals forces is present in the σ-profile. The presented theoretical DFT calculation in combination with the ANN mathematical tool can be easily extended to other π-conjugated, electronic material classes and offers a fast and reliable toolbox for future pathways that may include the design of green ink formulations for solution-processed optoelectronic devices.
Keywords: Engineering controlled terms: Computation theory; Design for testability; Fullerenes; Molecular dynamics; Neural networks; Optoelectronic devices; Solubility; Van der Waals forces Computational approach; Continuum solvation models; Electronic materials; Environmentally benign; Hansen solubility parameters; Molecular dynamics calculation; Numerical approaches; Solubility parameters Engineering main heading: Density functional theory

Correlative relationship between nanomorphology, crystallinity, texture and device efficiency of organic BHJ solar cells studied by energy-filtered TEM - Harreiß, Christina; Wu, Mingjian; Langner, Stefan; Rechberger, Stefanie; Will, Johannes; Brabec, Christoph; Spiecker, Erdmann (Microscopy and Microanalysis, 2021)

Crystal-structure of active layers of small molecule organic photovoltaics before and after solvent vapor annealing - Berlinghof, Marvin; Langner, Stefan; Harreiß, Christina; Schmidt, Ella; Siris, Rita; Bertram, Florian; Shen, Chen; Will, Johannes; Schindler, Torben; Prihoda, Annemarie; Rechberger, Stefanie; Duesberg, Georg; et al. (Zeitschrift fur Kristallographie - Crystalline Materials, 2020)
It is demonstrated by a detailed structural analysis that the crystallinity and the efficiency of small molecule based organic photovoltaics can be tuned by solvent vapor annealing (SVA). Blends made of the small molecule donor 2,2′-[(3,3′″,3″″,4′-tetraoctyl[2,2′:5′,2″:5″,2′″:5′″,2″″-quinquethiophene]-5,5″″-diyl)bis[(Z)-methylidyne(3-ethyl-4-oxo-5,2-thiazolidinediylidene)]]bis-propanedinitrile (DRCN5T) and the acceptor [6,6]-phenyl C71 butyric acid methyl ester (PC 71 BM) were annealed using solvent vapors with either a high solubility for the donor (tetrahydrofuran), the acceptor (carbon disulfide) or both (chloroform). The samples were analyzed by grazing-incidence wide-angle X-ray scattering (GIWAXS), electron diffraction, X-ray pole figures, and time-of-flight secondary ion mass spectrometry (ToF-SIMS). A phase separation of DRCN5T and PC 71 BM is induced by SVA leading to a crystallization of DRCN5T and the formation of a DRCN5T enriched layer. The DRCN5T crystallites possess the two dimensional oblique crystal system with the lattice parameters a = 19.2 Å, c = 27.1 Å, and β = 111.1° for the chloroform case. No major differences in the crystal structure for the other solvent vapors were observed. However, the solvent choice strongly influences the size of the DRCN5T enriched layer. Missing periodicity in the [010]-direction leads to the extinction of all Bragg reflections with k ≠ 0. The annealed samples are randomly orientated with respect to the normal of the substrate (fiber texture

Determination of the P3HT:PCBM solubility parameters via a binary solvent gradient method: Impact of solubility on the photovoltaic performance - Machui, Florian; Langner, Stefan; Zhu, Xiangdong; Abbott, Steven; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2012)
We discuss an alternative route to determine the solubility parameters of two prototype organic semiconductors, namely the semi-crystalline polymer poly-(3-hexylthiophene-2,5-diyl) (P3HT) and the methano-fullerene derivative [6,6]-phenyl-C -butyric acid methyl ester (PCBM). The HSP (Hansen solubility Parameters) derived by this novel method are compared to the findings derived from the classical multi-solvent method to determine the HSP, and significantly higher accuracy is found. For this novel approach we designed two component solvent blend systems, being composed by mixing a solvent with a non-solvent. Varying the composition of the solvent non-solvent blends from 0% to 100% gradually converts a solvent into a non-solvent. This very accurate control of the dispersive, polar and hydrogen contributions to the overall solubility now allows determining the Hansen sphere for P3HT and PCBM with much higher accuracy. The transition from a solvent into a non-solvent was further followed by solar cell investigations. Comparing the solubility studies with device investigations allows identifying the processing limits of solvent systems. © 2012 Elsevier B.V. All rights reserved.
Keywords: Conjugated polymers; Fullerenes; Hansen solubility parameters; Ink formulations; Organic photovoltaics; Solvent blends

Discovery of temperature-induced stability reversal in perovskites using high-throughput robotic learning - Zhao, Yicheng; Hauch, Jens; Zhang, Jiyun; Xu, Zhengwei; Sun, Shijing; Langner, Stefan; Hartono, Noor Titan Putri; Heumüller, Thomas; Hou, Yi; Elia, Jack; Li, Ning; Matt, Gebhard; et al. (Nature Communications, 2021)
Stability of perovskite-based photovoltaics remains a topic requiring further attention. Cation engineering influences perovskite stability, with the present-day understanding of the impact of cations based on accelerated ageing tests at higher-than-operating temperatures (e.g. 140°C). By coupling high-throughput experimentation with machine learning, we discover a weak correlation between high/low-temperature stability with a stability-reversal behavior. At high ageing temperatures, increasing organic cation (e.g. methylammonium) or decreasing inorganic cation (e.g. cesium) in multi-cation perovskites has detrimental impact on photo/thermal-stability; but below 100°C, the impact is reversed. The underlying mechanism is revealed by calculating the kinetic activation energy in perovskite decomposition. We further identify that incorporating at least 10 mol.% MA and up to 5 mol.% Cs/Rb to maximize the device stability at device-operating temperature (<100°C). We close by demonstrating the methylammonium-containing perovskite solar cells showing negligible efficiency loss compared to its initial efficiency after 1800 hours of working under illumination at 30°C.
CRIS-Team Scopus Importer:2021-05-21

Elucidating the Full Potential of OPV Materials Utilizing a High-Throughput Robot-Based Platform and Machine Learning - Du, Xiaoyan; Lüer, Larry; Heumüller, Thomas; Wagner, Jerrit; Berger, Christian; Osterrieder, Tobias; Wortmann, Jonas; Langner, Stefan; Vongsaysy, Uyxing; Bertrand, Melanie; Li, Ning; Stubhan, Tobias; et al. (Joule, 2021)
Evaluating the potential of organic photovoltaic (OPV) materials and devices for industrial production is a multidimensional optimization process with an incredibly large parameter space. Here, we demonstrate automated OPV material and device characterization in terms of efficiency and photostability. Gaussian process regression (GPR) prediction based on optical absorption features guided the optimization process with promising prediction accuracy for PV parameters and burn-in losses. With ∼100 process conditions, screening for efficiency and photostability can be finished within 70 h. The highest power conversion efficiency (PCE) of 14% was achieved by fully automated device fabrication in air with a model material system PM6:Y6. Improving molecular ordering has been identified as the most promising motif for further efficiency optimization. Thin active layers combined with medium thermal annealing temperature are favorable to simultaneously improve efficiency and suppress burn-in losses. The platform and protocol may be expanded to any solution-processed organic semiconductor and interface materials.
CRIS-Team Scopus Importer:2021-02-05
Keywords: automation; efficiency; high-throughput methods; machine learning; organic photovoltaics; photostability; processing optimization

Exploring the Stability of Novel Wide Bandgap Perovskites by a Robot Based High Throughput Approach - Chen, Shi; Hou, Yi; Chen, Haiwei; Tang, Xiaofeng; Langner, Stefan; Li, Ning; Stubhan, Tobias; Levchuk, Ievgen; Gu, Ening; Osvet, Andres; Brabec, Christoph (Advanced Energy Materials, 2017)
Currently, lead-based perovskites with mixed multiple cations and hybrid halides are attracting intense research interests due to their promising stability and high efficiency. A tremendous amount of 3D and 2D perovskite compositions and configurations are causing a strong demand for high throughput synthesis and characterization. Furthermore, wide bandgap (≈1.75 eV) perovskites as promising top-cell materials for perovskite–silicon tandem configurations require the screening of different compositions to overcome photoinduced halide segregation and still yielding a high opencircuit voltage (Voc). Herein, a home-made high throughput robot setup is introduced performing automatic perovskite synthesis and characterization. Subsequently, four kinds of compositions (i.e., cation mixtures of Cs–methylammonium (MA), Cs– formamidinium (FA), MA–FA, and FA–MA) with an optical bandgap of ≈1.75 eV are identified as promising device candidates. For Cs–MA and Cs–FA films it is found that the Br–I phase segregation indeed can be overcome. Moreover, Cs–MA, MA–FA, and Cs–FA based devices exhibit an average Voc of 1.17, 1.17, 1.12 V, and their maximum values approached 1.18, 1.19, 1.14 V, respectively, which are among the highest Voc (≈1.2 V) values for ≈40% Br perovskite. These findings highlight that the high throughput approach can effectively and efficiently accelerate the invention of novel perovskites for advanced applications.

Exploring the Steric Hindrance of Alkylammonium Cations in the Structural Reconfiguration of Quasi-2D Perovskite Materials Using a High-throughput Experimental Platform - Zhang, Jiyun; Wu, Jianchang; Langner, Stefan; Zhao, Baolin; Xie, Zhiqiang; Hauch, Jens; Afify, Hany A.; Barabash, Anastasia; Luo, Junsheng; Sytnyk, Mykhailo; Meng, Wei; Zhang, Kaicheng; et al. (Advanced Functional Materials, 2022)
Reduced-dimensional (2D or quasi-2D) perovskites have recently attracted considerable interest due to their superior long-term stability. The nature of the intercalating cations plays a key role in determining the physicochemical properties and stability of the quasi-2D perovskites. Here, the thermal stability of a series of 2D Ruddlesden−Popper (RP) perovskites is studied using seven types of intercalating cations with increasing linear carbon-chain length from ethylammonium (EA) to n-dodecylammonium (DA) through a high-throughput platform. The results show that long-chain cations in quasi-2D perovskite films lead to strong steric hindrance between adjacent perovskite domains, thus suppressing Ostwald ripening during the thermal-aging process. For short-chain cations, increased-dimensional phase redistribution during the aging period is observed, which can benefit a concomitant regeneration of the 3D/3D-like perovskite phases. The impact of steric hindrance on structural reconfiguration and the subsequent phase redistribution in quasi-2D perovskites are systematically characterized by UV–vis absorption spectra, photoluminescence spectra, and X-ray diffraction patterns. Due to the steric hindrance effect, an optimal chain length is found to maximize film stability by balancing the water/oxygen resistance and increased-dimensional phase redistribution. This work provides new insight into the thermal stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-09-02
Keywords: 2D perovskite materials; high-throughput platform; stability performance; steric hindrance; steric structure and reconfiguration

Flexible sample cell for real-time GISAXS, GIWAXS and XRR: design and construction - Berlinghof, Marvin; Bär, Christian; Haas, D.; Bertram, F.; Langner, Stefan; Osvet, Andres; Chumakov, A.; Will, Johannes; Schindler, Torben; Zech, Tobias; Brabec, Christoph; Unruh, Tobias (Journal of Synchrotron Radiation, 2018)
Since the properties of functional materials are highly dependent on their specific structure, and since the structural changes, for example during crystallization, induced by coating and annealing processes are significant, the study of structure and its formation is of interest for fundamental and applied science. However, structure analysis is often limited to ex situ determination of final states due to the lack of specialized sample cells that enable real-time investigations. The lack of such cells is mainly due to their fairly complex design and geometrical restrictions defined by the beamline setups. To overcome this obstacle, an advanced sample cell has been designed and constructed; it combines automated doctor blading, solvent vapor annealing and sample hydration with real-time grazing-incidence wide- and small-angle scattering (GIWAXS/GISAXS) and X-ray reflectivity (XRR). The sample cell has limited spatial requirements and is therefore widely usable at beamlines and laboratory-scale instruments. The cell is fully automatized and remains portable, including the necessary electronics. In addition, the cell can be used by interested scientists in cooperation with the Institute for Crystallography and Structural Physics and is expandable with regard to optical secondary probes. Exemplary research studies are presented, in the form of coating of P3HT:PC61PM thin films, solvent vapor annealing of DRCN5T:PC71BM thin films, and hydration of supported phospholipid multilayers, to demonstrate the capabilities of the in situ cell.
Keywords: in situ; GIWAXS; GISAXS; XRR; thin film

Fully Printed Infrared Photodetectors from PbS Nanocrystals with Perovskite Ligands - Yousefiamin, Amirabbas; Killilea, Niall Andrew; Sytnyk, Mykhailo; Maisch, Philipp; Tam, Kwok-Kan; Egelhaaf, Hans-Joachim; Langner, Stefan; Stubhan, Tobias; Brabec, Christoph; Rejek, Tobias; Halik, Marcus; Poulsen, Katharina; et al. (ACS nano, 2019)
Colloidal nanocrystals from PbS are successfully applied in highly sensitive infrared photodetectors with various device architectures. Here, we demonstrate all-printed devices with high detectivity (similar to 10(12) cm Hz(1/2) /W) and a cut-off frequency of >3 kHz. The low material consumption (<0.3 mg per detector) and short processing time (14 s per detector) enabled by the automated printing promises extremely low device costs. To enable all-printed devices, an ink formulation was developed based on nanocrystals stabilized by perovskite-like methylammonium iodobismuthate ligands, which are dispersed in a ternary solvent. Fully inkjet printed devices based on this solvent were achieved with printed silver electrodes and a ZnO interlayer. Considerable improvements were obtained by the addition of small amounts of the polymer poly(vinylpyrrolidone) to the ink. The polymer improved the colloidal stability of the ink and its film-formation properties and thus enabled the scalable printing of single detectors and detector arrays. While photoconductors were shown here, the developed ink will certainly find application in a series of further electronic devices based on nanocrystals from a broad range of materials.
Keywords: colloidal nanocrystals; infrared detectors; inkjet printing; PbS; solution processing

High-performance semitransparent perovskite solar cells with solution-processed silver nanowires as top electrodes - Guo, Fei; Azimi, Seyed Hamed; Hou, Yi; Przybilla, Thomas; Hu, Mengyao; Bronnbauer, Carina; Langner, Stefan; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Nanoscale, 2015)
In this work, we report efficient semitransparent perovskite solar cells using solution-processed silver nanowires (AgNWs) as top electrodes. A thin layer of zinc oxide nanoparticles is introduced beneath the AgNWs, which fulfills two essential functionalities: it ensures ohmic contact between the PC60BM and the AgNWs and it serves as a physical foundation that enables the solution-deposition of AgNWs without causing damage to the underlying perovskite. The as-fabricated semitransparent perovskite cells show a high fill factor of 66.8%, V-oc = 0.964 V, J(sc) = 13.18 mA cm(-2), yielding an overall efficiency of 8.49% which corresponds to 80% of the reference devices with reflective opaque electrode

Infrared Absorption Imaging of Water Ingress Into the Encapsulation of (Opto-)Electronic Devices - Hepp, Johannes; Vetter, Andreas; Langner, Stefan; Woiton, Michael; Jovicic, Gordana; Burlafinger, Klaus; Hauch, Jens; Camus, Christian; Egelhaaf, Hans-Joachim; Brabec, Christoph (IEEE Journal of Photovoltaics, 2019)
Water ingress into the encapsulation of electronic devices is a serious issue, especially for organic and perovskite-based electronics. In order to guide the development of suitable barrier materials and design, a reliable, fast, and non-destructive analysis tool is required. In this work, an imaging setup is presented, which is based on selective infrared (IR) radiation sources and a mid-IR sensitive camera that uses the absorption hand of water around 1920 nm and a reference band. This system enables us to monitor the distribution of water concentration inside the packaging of devices and its change over time. Our measurement is capable of detecting the local presence of water down to the mg/m(2) concentration range in a wide variety of encapsulation materials. The new tool allows identifying the pathways of moisture ingress into the encapsulation along with the corresponding diffusion coefficient. Thus, it provides fast and reliable analysis of humidity related failure mechanisms, and consequently helps to improve the design of encapsulation materials and processes.
Keywords: Degradation; diffusion processes; optical signal detection; organic photovoltaics (PVs); packaging

In Situ and Ex Situ Energy-Filtered Transmission Electron Microscopy Studies on the Nanomorpholgy Evolution of Organic Bulk Heterojunction Solar Cells - Harreiß, Christina; Langner, Stefan; Berlinghof, Marvin; Rechberger, Stefanie; Will, Johannes; Unruh, Tobias; Brabec, Christoph; Spiecker, Erdmann (Microscopy and Microanalysis, 2019)

Intercalating-Organic-Cation-Induced Stability Bowing in Quasi-2D Metal-Halide Perovskites - Zhang, Jiyun; Langner, Stefan; Wu, Jianchang; Kupfer, Christian; Lüer, Larry; Meng, Wei; Zhao, Baolin; Liu, Chao; Daum, Manuel; Osvet, Andres; Li, Ning; Halik, Marcus; et al. (ACS Energy Letters, 2022)
Quasi-2D metal-halide perovskites with Ruddlesden-Popper structures have shown promising stability due to the protective effects of the intercalating organic cations. However, a systematic study of the effect of intercalating organic cations on stability has rarely been reported. Here we use a high-throughput-robot platform to fabricate over 300 perovskite films and study the effect of cations and their concentrations on the thermal stability of perovskite films. We find that approximately 20-25 mol % of intercalating organic cations into MAPbI3 (nominal n = 4/5) can maximize the film stability, while higher/lower concentrations lead to inferior stability, which is termed stability bowing in analogy to band-gap bowing. A model with two competitive effects of the intercalating organic cation (better protection vs more defects) is proposed to rationalize this behavior. We anticipate this work to provide new insights into the stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-02-11

Introducing a New Potential Figure of Merit for Evaluating Microstructure Stability in Photovoltaic Polymer-Fullerene Blends - Perea, Jose Dario; Langner, Stefan; Salvador, Michael Filipe; Sanchez-Lengeling, Benjamin; Li, Ning; Zhang, Chaohong; Jarvas, Gabor; Kontos, Janos; Dallos, Andras; Aspuru-Guzik, Alan; Brabec, Christoph (Journal of Physical Chemistry C, 2017)
A theoretical understanding of the microstructure of organic semiconducting polymers and blends is vital to further advance the optoelectronic device performance of organic electronics. We outline the theoretical framework of a combined numerical approach based on polymeric solution theory to study the microstructure of polymer:small molecule blends. We feed the results of ab initio density functional theory quantum chemistry calculations into an artificial neural network for the determination of solubility parameters. These solubility parameters are used to calculate Flory-Huggings intermolecular parameters. We further show that the theoretical values are in line with experimentally determined data. On the basis of the Flory-Huggings parameters, we establish a figure of merit as a relative metric for assessing the phase diagrams of organic semiconducting blends in thin films. This is demonstrated for polymer:fullerene blend films on the basis of the prototypical polymers poly(3-hexylthiophene-2,5-diyl) (P3HT) and poly[(5,6-difluoro-2,1,3-benzothiadiazol-4,7-diyl)-alt-(3,3-di(2-octyldodecyl)-2,2,5,2;5,2-quaterthiophen-5,5-diyl)] (PffBT4T-2OD). After confirming the applicability of our model with a broader range of materials and differences in molecular weight, we suggest that this combined model should be able to inform design criteria and processing guidelines for existing and new high performance semiconducting blends for organic electronics applications with ideal and stable solid state morphology. (Graph Presented). © 2017 American Chemical Society.
Keywords: BlendingCalculationsDensity functional theoryFullerenesMicrostructureNeural networksOptoelectronic devicesOrganic polymersPolymer filmsPolymersQuantum chemistrySemiconducting filmsSemiconducting polymersSolubility

Luminescence Analysis of PV-Module Soiling in Germany - Doll, Bernd; Forberich, Karen; Hepp, Johannes; Langner, Stefan; Buerhop-Lutz, Claudia; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (IEEE Journal of Photovoltaics, 2021)
Energy losses of photovoltaic (PV) plants because of soiling are a problem in all regions, including Germany. Soft soiling, caused by a uniform dust film, is shading a PV module and is reducing yield depending on the thickness of the debris layer. Hard soiling, caused by agglomerations of dust or dirt, only covers parts of a PV module, and it causes local shading. A spot check of modules from different PV power plants in Germany revealed a power reduction because of soft- and hard soiling of up to 6%. Determination of soiling type and amount is a prerequisite for decisions about cleaning and for optimizing yield. In this article, we show that luminescence imaging can be used to detect and characterize soiling and quantify losses. For this purpose, we compare luminescence images before and after cleaning and we show that soiling becomes detectable and power losses quantifiable from difference images. We also show that the impact of hard soiling can be quantified from a single photoluminescence (PL) image. This technique may enable a fully automated quantification of power losses because of hard soiling in PV- modules and strings in the future.
CRIS-Team WoS Importer:2021-12-31

Nanowire Interconnects for Printed Large-Area Semitransparent Organic Photovoltaic Modules - Guo, Fei; Kubis, Peter; Przybilla, Thomas; Spiecker, Erdmann; Hollmann, Andre; Langner, Stefan; Forberich, Karen; Brabec, Christoph (Advanced Energy Materials, 2015)
Semitransparent organic photovoltaic (OPV) cells promise applications in various transparent architectures where their opaque counterparts cannot contribute. Realizing practical applications of this technology requires the manufacturing of large-area modules without significant performance loss compared to the lab-scale devices. In this work, efficient semitransparent OPV modules based on ultrafast laser patterning on both glass and flexible substrates are reported. Solution-processed metallic silver nanowires (AgNWs) are used as transparent top electrodes. The efficient low-ohmic contact of the interconnects between the top AgNWs and the bottom electrode in combination with high-precision laser beam positioning system allow to fabricate semitransparent modules with high electrical fill factor of approximate to 63% and a remarkable geometric fill factor exceeding 95%, respectively. These results represent an important progress toward upscaling of high-performance OPV modules with reduced production costs.

Overcoming the Thermal Instability of Efficient Polymer Solar Cells by Employing Novel Fullerene-Based Acceptors - Zhang, Chaohong; Mumyatov, Alexander; Langner, Stefan; Perea Ospina, Jose Dario; Kassar, Thaer; Min, Jie; Ke, Lili; Chen, Haiwei; Gerasimov, Kirill L.; Anokhin, Denis V.; Ivanov, Dimitri A.; Ameri, Tayebeh; et al. (Advanced Energy Materials, 2017)
Solution-processed organic solar cells with promising photovoltaic performance and extraordinary high thermal stability are achieved by employing novel fullerene-based acceptors in combination with two state-of-the-art polymer donors. The findings demonstrated in this work underline the necessity and importance of novel acceptor design rules for highly efficient organic solar cells with excellent device stability.
Keywords: Miscibility; Morphological analysis; Novel fullerene-based acceptors; Organic photovoltaics; Thermal stability

P3HT: Non-fullerene acceptor based large area, semi-transparent PV modules with power conversion efficiencies of 5%, processed by industrially scalable methods - Strohm, S.; Machui, F.; Langner, Stefan; Kubis, P.; Gasparini, Nicola; Salvador, Michael Filipe; Mcculloch, I.; Egelhaaf, H. -J.; Brabec, Christoph (Energy and Environmental Science, 2018)

Robot-Based High-Throughput Engineering of Alcoholic Polymer: Fullerene Nanoparticle Inks for an Eco-Friendly Processing of Organic Solar Cells - Xie, Chen; Tang, Xiaofeng; Berlinghof, Marvin; Langner, Stefan; Chen, Shi; Späth, Andreas; Li, Ning; Fink, Rainer; Unruh, Tobias; Brabec, Christoph (ACS Applied Materials and Interfaces, 2018)
Development of high-quality organic nanoparticle inks is a significant scientific challenge for the industrial production of solution processed organic photovoltaics (OPVs) with eco-friendly processing methods. In this work, we demonstrate a novel, robot-based, high throughput procedure performing automatic poly(3-hexylthio-phene-2,5-diyl) and indene-C-60 bisadduct nanoparticle ink synthesis in nontoxic alcohols. A novel methodology to prepare particle dispersions for fully functional OPVs by manipulating the particle size and solvent system was studied in detail. The ethanol dispersion with a particle diameter of around 80-100 nm exhibits reduced degradation, yielding a power conversion efficiency of 4.52%, which is the highest performance reported so far for water/alcohol-processed OPV devices. By successfully deploying the high-throughput robot-based approach for an organic nanoparticle ink preparation, we believe that the findings demonstrated in this work will trigger more research interest and effort on eco-friendly industrial production of OPVs.
Keywords: organic photovoltaics; eco-friendly industrial production; robot-based systems; high-throughput organic nanoparticle synthesis; stable organic nanoparticle inks; organic nanoparticle size control

Robot-Based High-Throughput Screening of Antisolvents for Lead Halide Perovskites - Gu, Ening; Tang, Xiaofeng; Langner, Stefan; Duchstein, Patrick; Zhao, Yicheng; Levchuk, Ievgen; Kalancha, Violetta; Stubhan, Tobias; Hauch, Jens; Egelhaaf, Hans-Joachim; Zahn, Dirk; Osvet, Andres; et al. (Joule, 2020)
Solution-based processing of photovoltaic materials has important advantages, including lower overall costs and easier upscaling of fabrication, where the solvents play an essential role. Antisolvent crystallization technique is often applied to achieve high-quality perovskite materials. However, the basic chemistry of the solvent-antisolvent crystallization is still not well understood. Besides, common antisolvents are toxic, and their number is limited. In this work, a novel robot-based method was used to screen the efficient antisolvents for different solvent-perovskite systems. 336 combinations of perovskite-solvent-antisolvent could be prepared and characterized by the integrated robotic platform in 2 days. In addition, we provided a detailed working mechanism of the solvent-antisolvent crystallization approach. Furthermore, hundreds of potential antisolvents were proposed based on high-throughput screening and simulation. Verification tests match well with theory, and all reported antisolvents used for photovoltaic device optimizations are within our predicted range of the Hansen space, indicating that the predictions are reliable. In terms of solution-processed lead halide perovskite optoelectrical materials, suitable antisolvent is essential for the crystallization and properties of final products. Conventional experiments of antisolvent selections are based on the manual time-consuming trial-error methods, which cannot meet today's increasing demands. In this work, a robot-based method was used to screen the antisolvents for different solvent-perovskite systems in a high-throughput manner to study the influence of interactions among the solvent molecules, cations, metal-halides, and antisolvents, to build an informative database, and to reveal the working mechanism and selection criteria of antisolvents. Besides, simulations based on the screening results provide hundreds of potential antisolvents. Corresponding verification tests evidenced that our predictions are reliable and vital for designing future efficient mixed solvent systems for the fabrication of perovskite optoelectrical materials. A robotic platform is adopted to conduct a comprehensive solvent engineering for making lead halide perovskites in a high-throughput manner. Deeper insights into the working mechanisms and selection criteria of antisolvents are investigated and summarized. In addition, a reliable antisolvent database is established, and verification tests match well with the theory. Furthermore, our work provides significant guidance for designing functional and environment-friendly mixed solvent systems to fabricate high-quality perovskite materials or devices.
CRIS-Team Scopus Importer:2020-08-21
Keywords: antisolvents; automated research; high-throughput method; lead halide complexes; lead halide perovskite; solvent engineering

Solubility and miscibility for diluted polymers and their extension to organic semiconductors - Perea Ospina, Jose Dario; Langner, Stefan; Ameri, Tayebeh; Brabec, Christoph (Encyclopedia of Physical Organic Chemistry, 6 Volume Set, Band 1, 2017)

Suppression of Thermally Induced Fullerene Aggregation in Polyfullerene-Based Multiacceptor Organic Solar Cells - Dowland, Simon A.; Salvador, Michael Filipe; Perea Ospina, Jose Dario; Gasparini, Nicola; Langner, Stefan; Rajoelson, Sambatra; Ramanitra, Hasina H.; Lindner, Benjamin; Osvet, Andres; Brabec, Christoph; Hiorns, Roger C.; Egelhaaf, Hans-Joachim (ACS Applied Materials and Interfaces, 2017)
A novel main-chain polyfullerene, poly[fullerene-alt-2,5-bis(octyloxy)terephthalaldehyde] (PPC4), is investigated for its hypothesized superior morphological stability as an electron-accepting material in organic photovoltaics relative to the widely used fullerene phenyl-C61-butyric acid methyl ester (PCBM). When mixed with poly(3-hexylthiophene-2,5-diyl) (P3HT), PPC4 affords low-charge-generation yields because of poor intermixing within the blend. The adoption of a multiacceptor system, by introducing PCBM into the P3HT:polyfullerene blend, was found to lead to a 3-fold enhancement in charge generation, affording power conversion efficiencies very close to that of the prototypical P3HT:PCBM binary control. Upon thermal stressing and in contrast to the P3HT:PCBM binary, photovoltaic devices based on the multiacceptor system demonstrated significantly improved stability, outperforming the control because of suppression of the PCBM migration and aggregation processes responsible for rapid device failure. We rationalize the influence of the fullerene miscibility and its implications on the device performance in terms of a thermodynamic model based on Flory-Huggins solution theory. Finally, the potential universal applicability of this approach for thermal stabilization of organic solar cells is demonstrated, utilizing an alternative low-band-gap polymer-donor system.
Keywords: fullerene aggregation; main-chain polyfullerenes; multi acceptor composite blend; organic photovoltaics; thermal stability

The Relevance of Solubility and Miscibility for the Performance of Organic Solar Cells - Langner, Stefan; Perea Ospina, Jose Dario; Zhang, Chaohong; Li, Ning; Brabec, Christoph (CRC Press, 2019)
This chapter introduces the approach to ab initio calculate the values based on computational methods, and a Figure of Merit to predict the microstructure stability of bulk heterojunction (BHJ) composites. It focuses on solute-liquid miscibility and solute-solute miscibility and explains the degradation mechanisms related to microstructure. The chapter provides a detailed insight into the theoretical, computational and experimental principles of mixing of organic semiconductors. The microstructure of a BHJ film is determined by the competition between thermodynamics and kinetics during the drying process. The chapter describes the M. L. Hansen solubility parameters (HSPs) can be visualized in a three dimensional coordinates system with the solubility parameters as axes. The mixing compatibility of a polymer and a fullerene is graphically represented by the values of thermodynamic variables when the equilibrium is established among the phases of a system.
CRIS-Team Scopus Importer:2023-03-07

The Relevance of Solubility and Miscibility for the Performance of Organic Solar Cells - Langner, Stefan; Perea Ospina, Jose Dario; Zhang, Chaohong; Li, Ning; Brabec, Christoph (Conjugated Polymers. Properties, Processing, and Applications, 2019)
This chapter introduces the approach to ab initio calculate the values based on computational methods, and a Figure of Merit to predict the microstructure stability of bulk heterojunction (BHJ) composites. It focuses on solute–liquid miscibility and solute–solute miscibility and explains the degradation mechanisms related to microstructure. The chapter provides a detailed insight into the theoretical, computational and experimental principles of mixing of organic semiconductors. The microstructure of a BHJ film is determined by the competition between thermodynamics and kinetics during the drying process. The chapter describes the M. L. Hansen solubility parameters (HSPs) can be visualized in a three dimensional coordinates system with the solubility parameters as axes. The mixing compatibility of a polymer and a fullerene is graphically represented by the values of thermodynamic variables when the equilibrium is established among the phases of a syst
CRIS-Team WoS Importer:2021-10-18

Time-Resolved Analysis of Dielectric Mirrors for Vapor Sensing - Gao, Shuai; Tang, Xiaofeng; Langner, Stefan; Osvet, Andres; Harreiß, Christina; Barr, Maissa; Spiecker, Erdmann; Bachmann, Julien; Brabec, Christoph; Forberich, Karen (ACS Applied Materials and Interfaces, 2018)
Dielectric mirrors based on bilayers of polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene (SEBS) and poly(vinyl alcohol) (PVA)-zirconium dioxide (ZrO2) nanocomposites are fabricated for vapor sensing. When exposed to specific solvent vapor, the layers of dielectric mirrors can gradually swell and cause a red-shift of the reflection band. Because PVA solely responds to water and SEBS is sensitive to several different types of organic solvents, the mirrors can respond to a large variety of solvents. The dual-functional hydrophilic ZrO2 nanoparticles are introduced to not only enlarge the refractive index contrast but also increase the permeability. Time-resolved measurements show that mirrors with nanoparticles have a significantly faster response than those without nanoparticles. Moreover, the dependence on relative humidity is studied for representative solvents, and several types of solvents are selected to show the dependence on the solvent-polymer interaction parameters at typical relative humidity, which allows one to predict the responsivity and selectivity of the sensors. © 2018 American Chemical Societ
Keywords: dielectric mirrors; distributed Bragg reflectors; vapor sensing; fully printed; time-resolved analysis

Understanding and Controlling the Evolution of Nanomorphology and Crystallinity of Organic Bulk-Heterojunction Blends with Solvent Vapor Annealing - Harreiß, Christina; Langner, Stefan; Wu, Mingjian; Berlinghof, Marvin; Rechberger, Stefanie; Will, Johannes; Conroy, Michele; Bangert, Ursel; Unruh, Tobias; Brabec, Christoph; Spiecker, Erdmann (Solar RRL, 2022)
Solvent vapor annealing (SVA) has been shown to significantly improve the device performance of organic bulk-heterojunction solar cells, yet the mechanisms linking nanomorphology, crystallinity of the active layer, and performance are still largely missing. Here, the mechanisms are tackled by correlating the evolution of nanomorphology, crystallinity, and performance with advanced transmission electron microscopy methods systematically. Model system of DRCN5T:PC71BM blends are SVA treated with four solvents differing in their donor and acceptor solubilities. The choice of solvent drastically influences the rate at which the maximum device efficiency establishes, though similar values can be achieved for all solvents. The donor solubility is identified as a key parameter that controls the kinetics of diffusion and crystallization of the blend molecules, resulting in an inverse relationship between optimal annealing time and donor solubility. For the highest efficiency, optimum domain size and single-crystalline nature of DRCN5T fibers are found to be crucial. Moreover, the π–π stacking orientation of the crystallites is directly revealed and related to the nanomorphology, providing insight into the charge carrier transport pathways. Finally, a qualitative model relating morphology, crystallinity, and device efficiency evolution during SVA is presented, which may be transferred to other light-harvesting blends.
Created from Fastlane, Scopus look-up
Keywords: crystallinity; EF-ED; EFTEM; nanomorphology; organic BHJ solar cells; small molecules; SVA

Understanding the correlation and balance between the miscibility and optoelectronic properties of polymer-fullerene solar cells - Zhang, Chaohong; Langner, Stefan; Mumyatov, Alexander V.; Anokhin, Denis V.; Min, Jie; Perea, Jose Dario; Gerasimov, Kirill L.; Osvet, Andres; Ivanov, Dimitri A.; Troshin, Pavel; Li, Ning; Brabec, Christoph (Journal of Materials Chemistry A, 2017)
Organic photovoltaics is one of the most promising technologies for sustainable green energy supply. Because of their high electron affinity and superior electron-transporting ability, fullerene-based materials are deemed as very strong electron-accepting components in organic solar cells. However, the most widely used fullerene-based acceptors, such as phenyl-C61-butyric acid methyl ester, exhibit limited microstructural stability and unsatisfactory thermal stability owing to their insufficient compatibility with organic donors. Here, we in-depth investigate the carrier dynamics along with structural evolution and analyze the acceptor loadings in optimized bulk-heterojunction (BHJ) solar cells as a function of the polymer-fullerene miscibility. The polymer-fullerene miscibility has more influential effects than the crystallinity of single components on the optimized acceptor:donor ratio in polymer-fullerene solar cells. The findings demonstrated in this work suggest that the balance between the miscibility of BHJ composites and their optoelectronic properties has to be carefully considered for future development and optimization of OPV solar cells based on BHJ composites. Miscibility is proposed in addition to crystallinity as a further design criterion for long lived and efficient solar cells. © 2017 The Royal Society of Chemistry.
Keywords: Engineering controlled terms: Butyric acidElectron affinityFullerenesHeterojunctionsOrganic solar cellsPolymer solar cellsPolymersSolubility Bulk heterojunction (BHJ)Electron transportingHigh electron affinitiesInfluential effectsMicrostructural stabilityOptoelectronic propertiesOrganic photovoltaicsStructural evolution Engineering main heading: Solar cells

Understanding the Microstructure Formation of Polymer Films by Spontaneous Solution Spreading Coating with a High-Throughput Engineering Platform - Wang, Rong; Lüer, Larry; Langner, Stefan; Heumüller, Thomas; Forberich, Karen; Zhang, Heyi; Hauch, Jens; Li, Ning; Brabec, Christoph (Chemsuschem, 2021)
An important step of the great achievement of organic solar cells in power conversion efficiency is the development of low-band gap polymer donors, PBDB−T derivatives, which present interesting aggregation effects dominating the device performance. The aggregation of polymers can be manipulated by a series of variables from a materials design and processing conditions perspective; however, optimization of film quality is a time- and energy-consuming work. Here, we introduce a robot-based high-throughput platform (HTP) that is offering automated film preparation and optical spectroscopy thin-film characterization in combination with an analysis algorithm. PM6 films are prepared by the so-called spontaneous film spreading (SFS) process, where a polymer solution is coated on a water surface. Automated acquisition of UV/Vis and photoluminescence (PL) spectra and automated extraction of morphological features is coupled to Gaussian Process Regression to exploit available experimental evidence for morphology optimization but also for hypothesis formulation and testing with respect to the underlying physical principles. The integrated spectral modeling workflow yields quantitative microstructure information by distinguishing amorphous from ordered phases and assesses the extension of amorphous versus the ordered domains. This research provides an easy to use methodology to analyze the exciton coherence length in conjugated semiconductors and will allow to optimize exciton splitting in thin film organic semiconductor layers as a function of processing.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Gaussian process regression; high-throughput engineering; microstructure morphology; organic photovoltaics; spontaneous film spreading

Water ingress in encapsulated inverted organic solar cells: Correlating infrared imaging and photovoltaic performance - Adams, Jens; Salvador, Michael Filipe; Lucera, Luca; Langner, Stefan; Spyropoulos, George D.; Fecher, Frank; Voigt, Monika; Dowland, Simon A.; Osvet, Andres; Egelhaaf, Hans-Joachim; Brabec, Christoph (Advanced Energy Materials, 2015)
Understanding the degradation and failure mechanisms of organic photovoltaic devices is a key requirement for this technology to mature toward a reliable product. Here, an investigation on accelerated temperature and moisture long-term stability testing (>20 000 h) of inverted and glass-encapsulated poly(3-hexylthiophene)/phenyl-C-butyric acid methyl ester solar cells is presented. The degradation kinetics is analyzed using the Arrhenius model and the resulting activation energy for the diffusion of water is measured to be ≈43 kJ mol. Through comparison of electroluminescence imaging, lock-in thermography, and photoluminescence mapping, the device performance is correlated with the loss of effective cell area and it is shown that the reaction of water at the hole extraction/active layer interface is likely to be the dominant cause for long-term device failure. The diffusion of water through the packaged solar cell is described using classical diffusion theory. Based on an analytical solution of a simple diffusion model, the diffusion coefficient is estimated to be 4 × 10 m s. A shelf life of 100 000 h is anticipated at 65 °C/85% RH using a 9.3 cm wide protective adhesive rim. The findings of this study may inform strategies for predicting lifetimes of organic solar cells and modules based on local in situ tracking of moisture-induced device performance loss using IR imaging. Lifetime limitations of current-generation inverted and encapsulated organic solar cells under damp heat conditions are identified by correlating photovoltaic device performance with lock-in IR imaging techniques. The combination of electroluminescence imaging and water diffusion modeling may inform strategies for predicting early performance losses in solar cells and modules.
Keywords: electroluminescence imaging; lock-in thermography; long-term stability; organic photovoltaics; water diffusion